Manufacturing and Control of a Robotic Device for Time-averaged Simulated Micro and Partial Gravity of a Cell Culture Environment - Kim, Yoon Jae; Lim, Min Hyuk; Jeon, Byoungjun; Choi, Dong Hyun; Lee, Haeri; Jeong, Ae Jin; Kim, Min Jung; Park, Ji Won; Ku, Ja-Lok; Jeong, Seung-Yong; Ye, Sang-Kyu; Kim, Youdan; et al. (International journal of control, automation, and systems, 2020)
Gravity is omnipresent for all objects on Earth. However, in an environment of different gravitational stress (e.g., microgravity or partial gravity), cells and organs show different biological responses. So, researchers have attempted to achieve micro- or partial gravity on Earth through various approaches, such as parabolic flight or free fall. However, the duration of such ground experiments is highly limited, making it very difficult to conduct time-consuming tasks, such as cell culture. Thus, a three-dimensional (3D) clinostat is utilized as an alternative for experiments on the International Space Station. It provides time-averaged simulated micro- and partial gravity by using mechanical frames with two rotating actuators. This study proposes novel control algorithms for simulating micro- and partial gravity and validates them by applying it to the control of a manufactured 3D clinostat. First, the novel algorithm for time-averaged simulated microgravity (taSMG) provided a more uniformly distributed gravity field by reducing two poles the gravity-concentrated areas. The taSMG with reduced poles provides isotropic gravitational patterns, from which it is possible to minimize the unnecessary effect due to nonuniformity of the gravity vector direction. Second, the other suggested novel algorithm for time-averaged simulated partial gravity (taSPG) controls the pole sizes asymmetrically to generate the intended size of partial gravity. The suggested algorithms are based on mathematical models rather than totally randomized motions. Therefore, the convergence of gravity values, in the rotating frame over time, can be analytically predicted with improved accuracy compared with previously reported algorithms. The developed 3D clinostat hardware and algorithms will effectively provide well-validated taSMG and taSPG for cell growth experiments in future studies for space medicine.